Chronic disease outcome metadata from German observational studies – public availability and FAIR principles - Schwedhelm, Carolina; Nimptsch, Katharina; Ahrens, Wolfgang; Hasselhorn, Hans Martin; Jöckel, Karl-Heinz; Katzke, Verena; Kluttig, Alexander; Linkohr, Birgit; Mikolajczyk, Rafael; Nöthlings, Ute; Perrar, Ines; Peters, Annette; et al. (Scientific data, 2023)
Metadata from epidemiological studies, including chronic disease outcome metadata (CDOM), are important to be findable to allow interpretability and reusability. We propose a comprehensive metadata schema and used it to assess public availability and findability of CDOM from German population-based observational studies participating in the consortium National Research Data Infrastructure for Personal Health Data (NFDI4Health). Additionally, principal investigators from the included studies completed a checklist evaluating consistency with FAIR principles (Findability, Accessibility, Interoperability, Reusability) within their studies. Overall, six of sixteen studies had complete publicly available CDOM. The most frequent CDOM source was scientific publications and the most frequently missing metadata were availability of codes of the International Classification of Diseases, Tenth Revision (ICD-10). Principal investigators’ main perceived barriers for consistency with FAIR principles were limited human and financial resources. Our results reveal that CDOM from German population-based studies have incomplete availability and limited findability. There is a need to make CDOM publicly available in searchable platforms or metadata catalogues to improve their FAIRness, which requires human and financial resources.